THE INFLUENCE OF NET PROFIT MARGIN AND CURRENT RATIO ON STOCK PRICE - Anggadini, Sri Dewi; Tarsiah, Eva (Jurnal Riset Akuntansi, 2017)
This research have purpose to examine empirically the effect on Net Profit Margin and Liquidity (Current Ratio) to Stock Price on Sub Sector Pharmaceutical Company Listed on IndonesiaStock Exchange Period 2012-2016. The problems that occur in Sub Sector Pharmaceutical Companyis the decrease of Stock Price but not followed by the increase of Net Profit Margin. Then the companyhas descreased Stock Price but not followed by the increase of Liquidity (Current Ratio). The research uses descriptive verification analysis method with population 10 companies from Sub Sector Pharmaceutical Companies. Sample selected by using purposive sampling, so thesample obtained to 8 companies with 40 financial reports from Sub Sector Pharmaceutical CompanyListed in Indonesia Stock Exchange Period 2012-2016. Technical of data analysis is multiple linearregression with SPSS 16.0 version as the application. The result of the analysis showed that Net Profit Margin has positive and significant effect to Stock Price, and Liquidity which measured by Current Ratio has Positive dan significant effect toStock Price.